Magnetic resonance imaging of myelin - Laule, Cornelia (Neurotherapeutics, 2007)
The ability to measure myelin in vivo has great consequences for furthering our knowledge of normal development, as well as for understanding a wide range of neurological disorders. The following review summarizes the current state of myelin imaging using MR. We consider five MR techniques that have been used to study myelin: 1) conventional MR, 2) MR spectroscopy, 3) diffusion, 4) magnetization transfer, and 5) T(2) relaxation. Fundamental studies involving peripheral nerve and MR/histology comparisons have aided in the interpretation and validation of MR data. We highlight a number of important findings related to myelin development, damage, and repair, and we conclude with a critical summary of the current techniques available and their potential to image myelin in vivo.